A Comparative study of microwave-induced pyrolysis of lignocellulosic and algal biomass. (August 2015) - Wang, Nan; Tahmasebi, Arash; Yu, Jianglong; Xu, Jing; Huang, Feng; Mamaeva, Alisa
Highlights: Microwave pyrolysis of algal and lignocellulosic biomass is studied. Activation energy for pyrolysis of samples was calculated by Coats–Redfern method. Temperatures as high as 1170 °C were achieved by mixing samples with lignite char. Bio-oil from lignocellulosic biomass contained more single-ring aromatics. Bio-oil from microalgae had a higher content of nitrogen-containing compounds. Abstract: Microwave (MW) pyrolysis of algal and lignocellulosic biomass samples were studied using a modified domestic oven. The pyrolysis temperature was recorded continuously by inserting a thermocouple into the samples. Temperatures as high as 1170 and 1015 °C were achieved for peanut shell and Chlorella vulgaris . The activation energy for MW pyrolysis was calculated by Coats–Redfern method and the values were 221.96 and 214.27 kJ/mol for peanut shell and C. vulgaris, respectively. Bio-oil yields reached to 27.7 wt.% and 11.0 wt.% during pyrolysis of C. vulgaris and peanut shell, respectively. The bio-oil samples from pyrolysis were analyzed by a gas chromatography–mass spectrometry (GC–MS). Bio-oil from lignocellulosic biomass pyrolysis contained more phenolic compounds while that from microalgae pyrolysis contained more nitrogen-containing species. Fourier transform infrared spectroscopy (FTIR) analysis results showed that concentration of OH, CH, CO, OCH3, and CO functional groups in char samples decreased significantly after pyrolysis.